2022
DOI: 10.3390/ijms232214294
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion Co-Loaded with XIAP siRNA and Gambogic Acid for Inhalation Therapy of Lung Cancer

Abstract: Lung cancer is a leading cause of cancer mortality worldwide, with a 5-year survival rate of less than 20%. Gambogic acid (GA) is a naturally occurring and potent anticancer agent that destroys tumor cells through multiple mechanisms. According to the literature, one of the most potent inhibitors of caspases and apoptosis currently known is the X-linked Inhibitor of Apoptosis Protein (XIAP). It is highly expressed in various malignancies but has little or no expression in normal cells, making it an attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In order to perform uptake studies in B16-F10 melanoma cells, IL, either blank or surface modified i.e., IL ST-MBS TRF, IL ST-PEG-MBS TRF, and IL B-16-F10 CMF were labelled with 0.1 mg/mL 6-coumarin (6-CUM) fluorescent probe [ 11 , 20 , 32 , 33 , 34 , 35 ]. To this aim 50 μL of a 2 mg/mL stock solution of 6-CUM in DMSO were added to 1 mL of nanoemulsion, followed by mixing with a micropipette.…”
Section: Methodsmentioning
confidence: 99%
“…In order to perform uptake studies in B16-F10 melanoma cells, IL, either blank or surface modified i.e., IL ST-MBS TRF, IL ST-PEG-MBS TRF, and IL B-16-F10 CMF were labelled with 0.1 mg/mL 6-coumarin (6-CUM) fluorescent probe [ 11 , 20 , 32 , 33 , 34 , 35 ]. To this aim 50 μL of a 2 mg/mL stock solution of 6-CUM in DMSO were added to 1 mL of nanoemulsion, followed by mixing with a micropipette.…”
Section: Methodsmentioning
confidence: 99%
“…At present, beyond their application in the delivery of chemotherapeutic agents such as erlotinib, docetaxel, curcumin and quercetin, NEs are also under development for RNA delivery systems ( 57 - 60 ). Xu et al ( 61 ) reported a cationic NE delivery system based on chitosan (CS), capable of encapsulating both the antitumor drug gambogic acid and anti-X-linked inhibitor of apoptosis protein siRNA. NEs, through efficient enhancement of gambogic acid solubility, and the CS-siRNA complexation via electrostatic interactions, achieve improved siRNA protection and rapid drug release upon intracellular entry through a pH-responsive proton sponge effect, facilitating enhanced therapeutic efficacy.…”
Section: Classification Of Existing Inhalation Formulationsmentioning
confidence: 99%
“…However, this study was performed in vitro only further evaluation in the animal model is necessary to confirm the efficacy and stability [ 115 ]. The chitosan-modified cationic nanoemulsions were prepared which are composed of gambogic acid (GA), a naturally occurring anticancer agent, and siRNA which are targeted against X-linked Inhibitor of Apoptosis Protein (XIAP) which are potent inhibitors of caspases/apoptosis [ 116 ]. Generally, most drugs/siRNAs have a long residence time in the lungs because of pulmonary delivery thereby having greater therapeutic effects compared to systemic administration.…”
Section: Nanoemulsionsmentioning
confidence: 99%